The Impact of Pandemics Sentiment on the Global Art Market - Wei Wang (Frontiers Media S.A., 2021)
This paper investigates the effects of pandemics sentiment (the World Pandemics Discussion Index) on the returns of the global art market from 1998Q1 to 2021Q2 at the global level. The Ordinary Least Squares and the Quantile Regression estimations indicate that global pandemics sentiment positively affects the returns of the global art market. This evidence means that investing in the art market can hedge the uncertainty shocks related to pandemics at the global level.